2017
DOI: 10.18632/oncotarget.19173
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics and eicosanoid analysis identified serum biomarkers for distinguishing hepatocellular carcinoma from hepatitis B virus-related cirrhosis

Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers in the world. It is a type of inflammation-related cancer that usually follows liver hepatitis that mostly caused by hepatitis B virus (HBV) in China. However, the metabolism disturbance of HCC and HBV-cirrhosis is not yet fully understood. In addition, there is little research on the relationships between inflammation mediators and HCC. In this study, we investigated serum metabolic abnormalities in HBV-cirrhosis and HCC patients through non-tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Multiple metabolomic studies on HBV+ and HCV+ patients have been reported. For HBV, the studies mostly sought biomarkers of the development of cirrhosis or HCC [ 24 , 46 , 47 , 48 , 49 ] or biomarkers simply of HBV infection itself [ 10 , 28 ]. Similar studies have been reported in the case of HCV for serum biomarkers of progression to HCC [ 21 , 22 , 23 ] and for hepatic fibrosis [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple metabolomic studies on HBV+ and HCV+ patients have been reported. For HBV, the studies mostly sought biomarkers of the development of cirrhosis or HCC [ 24 , 46 , 47 , 48 , 49 ] or biomarkers simply of HBV infection itself [ 10 , 28 ]. Similar studies have been reported in the case of HCV for serum biomarkers of progression to HCC [ 21 , 22 , 23 ] and for hepatic fibrosis [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the HCC group showed a significant increased Alfa fetoprotein (AFP) level compared to CLD patients (p = 0.02), as well as prothrombin time expressed as an international normalized ratio (INR) (p = 0.005) and decreased level of hemoglobin (p = 0.011). 0.311 (2) Alanine transaminase (IU/L) Mean (range) 56 58 27 0.878 (a) 0.003 (2) Aspartate transaminase (IU/L) Mean (range) 65 48 26 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) 0.115 (a) 0.001 (2) Hemoglobin (g/L) Mean (range)…”
Section: Characteristics Of Subjectsmentioning
confidence: 99%
“…Gas chromatography/mass spectrometry (GC/MS) provided good coverage of primary metabolism in HCC ranging from energy metabolism [14] to glycolysis, TCA metabolites, purines, and lipids [30,31]. Specifically, GC/MS revealed alterations in amino acids, sugars, fatty acids, and other macromolecules in biofluids of HCC patients [22,25,[32][33][34][35][36]. However, none of these earlier studies combined analyses of both tissues and biofluids for detailing the pathogenesis of HCC in patients.…”
Section: Introductionmentioning
confidence: 99%
“…HBV infection decrease ATP levels in hepatocytes . Several other metabolites from mitochondria, in particular, citrate and succinate, are implicated in the pathological processes of viral hepatitis and cirrhosis . Given the complexity, whether it is a sequential or causal relationship between mitochondrial alteration and hepatitis remains unclear.…”
Section: Introductionmentioning
confidence: 99%